Cognitive-behavioral therapy for chronic worry - Leahy, Robert L. (Henry Stewart Talks, 2021)
Anxiety, Cognitive Behavioral Therapy (CBT), Generalized Anxiety Disorder (GAD), Theoretical models of worry, Chronic worry, CBT for chronic worry, Mindfulness, Psychology